2017
DOI: 10.1039/c7dt00132k
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of CS2- and SCNPh-adducts of the pyramidal phosphinidene-bridged complex [Mo2Cp(μ–κ115-PC5H4)(CO)26-HMes*)(PMe3)]

Abstract: The title complex reacted readily with CS 2 and SCNPh to give the phosphinidenecumulene adducts [Mo 2 Cp{-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…106 o ). This is also reflected in the observation, for the corresponding 13 C NMR resonances, of a relatively high coupling of ca. 28 Hz with both P atoms of the molecule.…”
Section: Scheme 5 Diazoalkane Derivatives Of 1 Amentioning
confidence: 77%
See 3 more Smart Citations
“…106 o ). This is also reflected in the observation, for the corresponding 13 C NMR resonances, of a relatively high coupling of ca. 28 Hz with both P atoms of the molecule.…”
Section: Scheme 5 Diazoalkane Derivatives Of 1 Amentioning
confidence: 77%
“…10 To further explore the complex reactivity of pyramidal phosphinidene complexes towards azides and diazoalkanes, we decided to study the reactivity of the dimolybdenum complex [Mo2Cp(- 1 : 1 , 5 -PC5H4)(CO)2( 6 -HMes*)(PMe3)] (1, Chart 2) towards these unsaturated organic molecules, which is the purpose of the present work. Previous studies have revealed that 1 displays a strong nucleophilicity that enables it to react under mild conditions with different C-based electrophiles such as organic anhydrides, 11 alkyl halides, 12 and S-containing cumulenes, 13 among other electrophiles. Thus, it could be anticipated that 1 might easily react with organic azides and diazoalkanes, although the subsequent evolution of the products following the initial PN bond formation step would be harder to predict, particularly because of the very different electronic environments of the Mo centers bound to the phosphinidene ligand in this molecule.…”
Section: Scheme 1 Azide and Diazoalkane Derivatives Of Pr-complexes Of Type A Amentioning
confidence: 99%
See 2 more Smart Citations
“…Tetrahydropyrimidines bearing a phosphoryl group are highly promising ligands for transition metal complexes . Phosphoryl thioamides have found broad applications as ligands for metal cations, polymerization initiators, hybrid materials building blocks, and multifunctional reagents . In recent years organophosphorus compounds have gained significant attention in organic synthesis, but convenient and valuable synthetic approaches for their preparation are still required .…”
Section: Introductionmentioning
confidence: 99%